SHARIAH COMPLIANCE OF BANGLADESHI ISLAMIC BANKS: DOES IT DIFFER ACROSS BANK MODALITIES? - Rahman, Syed Mohammad Khaled; Chowdhury, Mohammad Ashraful Ferdous; Hossain, Md. Mofazzal; Islam, Fakrul; Mim, Tanvin Hossin; Nirjon, Nazmul Alam (Journal of Islamic Monetary Economics and Finance, 2024)
This study assesses the degree of Shariah compliance of different Islamic banking modalities in Bangladesh from the perspectives of investment clients, depositors, and bankers. It adopts a structured questionnaire developed based on AAOIFI standards to gather data from 392 respondents. ANOVA tests and t-tests are applied to identify significant Shariah non-compliance areas and differences in Shariah compliance scores among different Islamic bank modalities. From investment clients’ perspective, it is seen that in every mode of investment except Ijarah, Shariah is explicitly violated throughout the Islamic banking industry. Significant Shariah non-compliance is seen in Bai-Murabaha, Bai-Muajjal, cash memos, and receipt and disbursement of goods, while Shariah is complied with in contract documents and client dealings. Bankers view all aspects except financial charges for delay to be Shariah compliant. From the depositors’ perspective, Shariah non-compliance is observed in the non-disclosure of information. There is no significant difference in Shariah compliance level between full-fledged and non-full-fledged Islamic banks. These findings should prove useful as a reference point for Bangladesh Bank, Islamic banks, policymakers, depositors, investors, and regulators to address Shariah non-compliance areas to ensure adherence to Shariah standards.AcknowledgmentThe authors would like to thank SUST Research Centre, for the funding that made this study possible.